2013
DOI: 10.1371/journal.pone.0074530
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Frontal-Parietal Resting-State Functional Connectivity Are Related to Disease Activity in Patients with Systemic Lupus Erythematosus

Abstract: Cerebral involvement is common in patients with systemic Lupus erythematosus (SLE) and is characterized by multiple clinical presentations, including cognitive disorders, headaches, and syncope. Several neuroimaging studies have demonstrated cerebral dysfunction during different tasks among SLE patients; however, there have been few studies designed to characterize network alterations or to identify clinical markers capable of reflecting the cerebral involvement in SLE patients. This study was designed to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 55 publications
1
26
2
Order By: Relevance
“…A summary of the studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) is depicted in Table 1. The largest original study contained 31 participants with SLE, whilst the smallest included 9 patients.…”
Section: Details Of Sle Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of the studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) is depicted in Table 1. The largest original study contained 31 participants with SLE, whilst the smallest included 9 patients.…”
Section: Details Of Sle Participantsmentioning
confidence: 99%
“…Disease activity and SLE damage index were obtained using SLE disease activity index (SLEDAI) (23), and systemic lupus international collaborating clinic damage index (SDI) (24) respectively. Disease activity was assessed in relation to functional alteration of different regions of the brain in three studies (13,15,20); whereas disease activity was stable in most of the other studies.…”
Section: Details Of Sle Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al 19 and Mackay et al 14 did not find any significant correlations between BOLD responses and disease activity as measured by serum biomarkers. Potential explanations for these nonsignificant results could be small numbers in the studies or the use of peripheral blood instead of cerebral spinal fluid (CSF) to assess biomarkers.…”
Section: Disease Activity and Immunological Findingsmentioning
confidence: 93%
“…15,[17][18][19][20][21] The majority of these reported that, behaviourally, SLE patients performed similarly to healthy controls 18-21 but showed significant differences in BOLD responses. During tasks examining working memory, learning and executive function increased BOLD responses were seen in areas such as the fusiform gyrus, prefrontal cortex, parietal regions, supplementary Only one study to date has directly compared SLE patients with cognitive impairment to those without using fMRI 16 and this study recruited childhoodonset patients only.…”
Section: Sle Patients Compared To Matched Healthy Controlsmentioning
confidence: 99%